IbM PENYUSUNAN PENILAIAN AUTENTIK BAGI GURU SEKOLAH DI PONPES DARUL FIKRI BAWEN - Joko Siswanto; Ernawati Saptaningrum; Joko Saefan; Siti Patonah; Duwi Nuvitalia (Universitas PGRI Semarang, 2015)
Abstract Low motivation of teachers in implementing authentic assessment becomes the basis for IbM team to carry out extension activities. Authentic assessment has actually been around a long time, but this issue arose when the curriculum was launched in 2013. During this time, most of the teachers at school in the field only make an assessment test course, not many people touched assessment tests that are written. Through activities of IbM Authentic Assessment Preparation Training for Teachers of Pesantren Darul Fikri Bawen, participants are expected to conduct a written assessment, performance assessment, product assessment projects, portfolio assessment, and manage the mark using computer-based process. Prior to socialization, teachers must first take pretest and post test. Pre test shows an average score of 89.65 while the average of post-test scores shows 97.6. During the activities, the participants felt helped and gave a positive response to organized similar activities. Keywords: Preparation, Assessment Authentic, Darul Fikri Boarding School Teacher